Korelasi Temperatur Udara dan Intensitas Radiasi Matahari Terhadap Performansi Mesin Pendingin Siklus Adsorpsi Tenaga Matahari - Tulus B. Sitorus; Farel H. Napitupulu; Himsar Ambarita (Cylinder : Jurnal Ilmiah Teknik Mesin, 2014)
One utilization of solar energy is adsorption refrigeration cycle where its performance is influenced by the air temperature and solar radiation intensity. This research aims to determine the effect of air temperature and solar radiation intensity on the performance of the solar adsorption refrigeration. This testing uses activated carbon adsorbent of 8 kg and 2 litres methanol refrigerant. The test results showed that the value of maximum COP obtained 0.064 and the minimum COP is 0.028. The lowest water temperatures that can be reached during the process of adsorption is 8.24oC. Correlation exists between the air temperature and solar radiation intensity on the COP value is significant so as to obtain mathematical equations. Air temperature correlation with the solar radiation intensity is 0.90 and the correlation of the intensity of solar radiation with the COP obtained -0.88. While the value of the correlation coefficient of the air temperature with COP is -0.95. Also obtained the coefficient of determination is 90.45%, which indicates that the influence of air temperature and solar radiation intensity on the coefficient of performance is 90.45%.